2021
DOI: 10.1016/j.jpeds.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Neonatal Magnetic Resonance Imaging and Short- and Long-Term Neurodevelopmental Outcomes in a Longitudinal Cohort of Very Preterm Children

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…It is possible that there are more subtle effects of hypercapnia on brain development that are not clinically apparent on the Bayley Scales at 2 years of age or that the effects seen on MRI at term equivalent age are transient. This would be consistent with a recently published study using a similar MRI scoring system, in which Jansen et al [17] found that MRI abnormalities at term equivalent age were independently associated with cognition, motor skills, and behavior…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…It is possible that there are more subtle effects of hypercapnia on brain development that are not clinically apparent on the Bayley Scales at 2 years of age or that the effects seen on MRI at term equivalent age are transient. This would be consistent with a recently published study using a similar MRI scoring system, in which Jansen et al [17] found that MRI abnormalities at term equivalent age were independently associated with cognition, motor skills, and behavior…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…PIH was significantly associated with severe functional disability, while PVL was less frequent and not associated with a poor outcome, probably due to the small number of children included in the study. Recent studies show that neonatal brain injury, assessed by a standardized magnetic resonance imaging (MRI) scoring system, is associated with short-term neurodevelopmental outcomes, but environmental factors are also important for cognitive development, especially for children with mild neonatal brain injury ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The typical pattern of brain injury experienced by preterm neonates is well described and includes intraventricular hemorrhage, venous infarction, periventricular echogenicity and leukomalacia, post-hemorrhagic ventricular dilatation, and hypoxic ischemic injury (Inder et al, 2021;Ortinau and Neil, 2015). However, only the more severe lesions evident on neuroimaging translate into longer term outcomes, with environmental factors exerting a greater influence on outcomes over time, especially in those with milder brain injury on imaging (Jansen et al, 2021). Furthermore, developmental delay in the preschool years does not necessarily portend later neurodevelopmental impairment in later years, particularly in the absence of neurosensory impairment or motor disability such as cerebral palsy (Hack et al, 2005).…”
Section: Brain Injury In Preterm Infantsmentioning
confidence: 99%